Transformational Leadership and Digital Skills in Higher Education Institutes: During the COVID-19 Pandemic - Hera Antonopoulou; Constantinos Halkiopoulos; Olympia Barlou; Grigorios N. Beligiannis (Emerging Science Journal, 2021)
Objectives: Recently, due to special conditions that the global community is experiencing (Covid-19), there is growing interest in research in educational leadership, especially in higher education, which will create an environment embedded in a collaborative culture, open to improvements, testing, and often unexpected challenges. Among the different forms of educational leadership, transformational leadership is recognized as the most appropriate for application in higher education, as it focuses on the division of leadership among academics with different skills in order to manage in a collective way the range of leadership duties required in different contexts. Methods/Analysis: This view is also reflected in this research paper, which focused on the degree of three specific forms of leadership (transformational leadership, transactional leadership, and leadership to be avoided) by members of the Senate of the University of Peloponnese. Descriptive and inductive methods of statistical analyses were applied for the interpretation of results. Findings: Notably, the findings indicate that leadership outcome has a strong positive correlation with transformational leadership and negative correlation with passive-to avoid leadership, confirming that higher transformational leadership implies greater efficiency and satisfaction for employees. Novelty/Improvement:A high degree of passive leadership coexists with the corresponding negative degree of implementation of digital leadership. Doi: 10.28991/esj-2021-01252 Full Text: PDF